Changes in Drinking Contexts over the Night Course: Concurrent and Lagged Associations with Adolescents' Nightly Alcohol Use. (2nd November 2020) - Finan, Laura J.; Lipperman‐Kreda, Sharon
Abstract : Background: Examining underage drinking contexts can advance the field of adolescent substance use prevention by supporting and informing interventions that can target adolescents in specific contexts. The current study examines how concurrent and lagged situational (i.e., alcohol availability and adult supervision), social (i.e., the number of people and presence of friends), and location (i.e., home vs other location) context characteristics change risks for alcohol use over the night course. Methods: Text messages with links to online surveys were used to collect ecological momentary assessment (EMA) data over 2 weekends from adolescents in California. Data were collected using adolescents' personal cell phones early and late in the evening and the following morning. Analyses were limited to adolescents with at least 1 drinking occasion during EMA ( N  = 58; Mage = 16.64, SD = 0.74; 48% female; 83% White). Results: Drinking earlier in the evening was positively associated with continued drinking over the night course. Context characteristics were found to play important concurrent and lagged roles in increasing the likelihood of alcohol use over evening hours. Conclusions: Findings indicated substantive concurrent and lagged social, situational, and location‐based contextual effects on adolescent alcohol use over the course of an evening. Importantly, context characteristics were differentially associated with alcohol use over the course of the evening. The fact that these contextual factors are modifiable suggests that the use of prevention strategies delivered to adolescents throughout the evening may reduce adolescents' drinking and related problems over the evening hours. Abstract : We examined how concurrent and lagged context characteristics change risks for alcohol use among adolescents over the night course. Using an ecological momentary assessment data, results show that situational (i.e., alcohol availability and adult supervision), social (i.e., the number of people and presence of friends), and location (i.e., home settings) context characteristics change risks for adolescents' nighttime alcohol use. Results suggest that the use of prevention strategies delivered throughout the evening hours may reduce adolescents' drinking and related problems.